Analisis Profitabilitas Usaha Peternakan Ayam Kampung Super di Kabupaten Jember - Muhammad Ardi Wiranata; Joko Irsan Sanyoto; Hariadi Subagja (Politeknik Negeri Jember, 2017)
This study aimed to determine the cost of management, day old chick cost, production, selling price to profit level, R / C ratio and Return on Investmen (ROI) ayam kampung super in Jember. The research method used was survey with 18 respondents in Jember. The data result were analyzed using multiple linear regression analysis and the following equations were Y = -1.90 â€“ 0.35X1 â€“ 1.22X2 + 0.23X3 + 2.26X4 + 0.11X5. This equation means every level of profit level by X1 (management cost) equal to -0.35, X2 (feed cost) equal to -1.22, X3 (seed cost) equal to 0.23, X4 (chicken production) equal to 2.26, X5 (chicken selling price) of 0.11. R / C ratio was 1.18, and ROI was 16%. The result of research showed that the most dominant factor influences to the profit level were Â feed cost, management cost and production. Profitability of this research 98% have been considered while factors outside this study 2%.